El universo en los mitos clásicos - Real Torres, Carolina; González Marrero, José Antonio, 1966- (1997)
Thepresentpaper will try toforget the differences that divide astronomy and astrology nowadays. We will do it with examples which make reference to the Classicalperiod. This topic will serve us to make a general revision ofthe Universe (mainly ofplanets) with the explicit aim ofproving that astronomy would not bear the importance that has in our days if in other historical eras astrology would not have participated in its conception.
Keywords: Mitología clásica